THE INFLUENCE OF CAREER DEVELOPMENT AND MOTIVATION ON EMPLOYEE PERFORMANCE AT BHAYANGKARA HOSPITAL - Lubis, Ria; Rinawati (jfpublisher, 2025)
This study aims to analyze the effect of career development and work motivation on employee performance at Polri Training Center Bhayangkara Hospital. The background of this study is based on the importance of human resource performance in ensuring the quality of health services, which is influenced by internal factors such as career development and work motivation. The approach used in this study is quantitative, with a survey method of the entire population of 165 hospital employees, consisting of medical and non-medical personnel. Data collection was conducted using a Likert scale closed questionnaire that had been tested for validity and reliability. Data analysis was conducted with multiple linear regression to test the simultaneous and partial effects between variables. The results showed that career development positively and significantly affects employee performance, with a significance value of 0.000 and a decisive contribution (β = 0.834). In contrast, work motivation did not show a statistically significant effect on employee performance (significance 0.122), although the direction of the relationship remained positive. The regression model has an R² value of 0.732, which means the career development and motivation variables together explain 73.2% of the variation in employee performance. This study emphasizes the importance of career development strategies in hospital HR management systems and the need for new approaches to improve the effectiveness of work motivation.